1986
DOI: 10.1002/ar.1092160303
|View full text |Cite
|
Sign up to set email alerts
|

SEM studies of acellular glomerular basement membrane in human diabetic glomerulopathy

Abstract: Previous transmission electron microscopic studies have demonstrated glomerular basement membrane (GBM) thickening and mesangial matrix (MM) expansion in chronic stages of diabetes. It is difficult, however, to achieve an appreciation of GBM surface features and distribution of MM in planar views. In the current study, autopsy human renal cortical tissue from patients with end-stage diabetic nephropathy were minced and rendered acellular with detergents prior to fixation, cryofracture, and preparation for ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…1986a. b;Carlson and Surerus, 1986;, Using this technique we have shown that normal monkey acellular GBMs resemble loops of capillary tufts [Carlson and Kenney. 1982;Carl son et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…1986a. b;Carlson and Surerus, 1986;, Using this technique we have shown that normal monkey acellular GBMs resemble loops of capillary tufts [Carlson and Kenney. 1982;Carl son et al.…”
Section: Discussionmentioning
confidence: 99%
“…both of which were described in diabetic human kidneys [Osterby et al. 1983;Carlson and Surerus. 1986], Our TEM studies also show' that in the diabetic monkey the expanded centrolobular MM is composed of a fibrillar network which surrounds larger fibrils including striated collagen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown in several species that at the level of LM, detergent treatment completely removed cellular components while glomerular ECM components, including various renal basement membranes, maintain their normal histoarchitectures Hinds, 1981, 1983;Carlson and Kenney, 1982;Carlson and Chatterjee, 1983;Carlson and Surerus, 1986;Marion and Carlson, 1989;Carlson et al, 1997). Likewise in the current study, whole acellular glomeruli from BB/DR, BB/DP h , and BB/ DP n animals at 1 year postonset of diabetes showed normal morphological features and were virtually indistinguishable with only minor increases in MM in BB/DP h kidneys.…”
Section: Light Microscopic Studiesmentioning
confidence: 99%